Usability Evaluation pada Aplikasi Taspen Otentikasi Berbasis System Usability Scale: Studi Kasus pada Pensiunan PNS - Kumalasari, R. Amalina Dewi; Tolle, Herman (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2024)
The Taspen Otentikasi application is a self-authentication service for retirees that uses combined biometric technology, which includes voice, face, and movement recognition from PT Taspen Persero. The aim of digitizing the authentication service into self-authentication is to make it easier for PT Taspen customers who are retirees and most of whom have entered old age so that they do not need to come to the Taspen payment partner office to carry out authentication at the counter and to avoid document forgery. To find out how easy a system can be used, usability testing can be carried out. One method that can be used in usability testing is the System Usability Scale (SUS). The total number of respondents used was 34 respondents. From this test, a score of 68.3 was obtained, which indicates that the system that has been built still needs to be refined so that it can be well received by users, especially elderly people.